Clinical Application and Influencing Factor Analysis of Metagenomic Next-Generation Sequencing (mNGS) in ICU Patients With Sepsis - Sun, Limin; Zhang, Shuguang; Yang, Ziyue; Yang, Fei; Wang, Zhenhua; Li, Hongqiang; Li, Yaoguang; Sun, Tongwen (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To analyze the clinical application and related influencing factors of metagenomic next-generation sequencing (mNGS) in sepsis patients in an intensive care unit (ICU). Methods: The study included 124 patients with severe sepsis admitted to the ICU in the First Affiliated Hospital of Zhengzhou University between June 2020 and September 2021. Two experienced clinicians took blood mNGS and routine blood cultures of patients meeting the sepsis diagnostic criteria within 24 hours of admission. General clinical data, biochemical indicators before the examination, comparison of mNGS results, consistency of blood culture, clinical consistency, the effect of influencing factors, clinical treatment plan adjustment, and the effect of adjusted outcome according to mNGS results were analyzed. Results: 1. mNGS positive rate was higher than traditional blood culture. 2. According to the relationship between mNGS detection results and clinical characteristics of patients, the negative rate of mNGS and the detection rate of single pathogen of mNGS were statistically different in sepsis patients with immune-related diseases, and there was no statistical difference in the detection rate of mixed infection. 3. This study explored the influencing factors related to positive results of the microbial test through univariate analysis, which showed that patients with immune-related underlying diseases had a lower proportion of double negative results.  Multivariate analysis by binary logistic regression showed that APACHE II score (odds ratio (OR)=1.156), immune-related diseases (OR=4.296), and hypertension (OR=3.413) were considered as positive independent factors for mNGS results. 4. Univariate and multivariate analyses of the effects on the prognosis of sepsis patients showed that the sequence number of mNGS microbe in univariate analysis had no effect on the prognosis; Whether the mNGS has a mixed infection is not directly related to the prognosis of the disease. Binary logistic regression analysis indicated that age (OR=5.624), female (OR=1.061), myoglobin (OR=1.005), and positive virus result (OR=9.186) were independent risk factors. Conclusion: mNGS is advantageous over traditional bacterial culture. mNGS can quickly acquire pathogens and find pathogens that are difficult to find in blood culture, which has positive significance for critically ill patients in ICU. mNGS positive rate was significantly higher than that of blood culture.